The limitation of the discovery rules of Court against the right of access to information in South Africa - Rashri Baboolal-Frank; Fola Adeleke (Revista Direito GV)
Abstract In South Africa, the Promotion of Access to Information Act 2 of 2000 (PAIA) gives effect to the right of access information in Section 32 of the South African Constitution (the Constitution). Section 7 of PAIA provides that PAIA does not apply to records required for criminal or civil proceedings after commencement of proceedings where access to that record is already provided for in any other law. Where records are obtained in contravention of Section 7, they are not admissible as evidence in criminal or civil proceedings. The aim of this paper is to determine whether the discovery rules of Court limit the constitutional right of everyone to access information. Consequently, the methodology employed in this paper involves a legal analysis namely: a limitations analysis utilising Section 36, the limitations clause of the Constitution. This paper further engages in case law analysis interpreting the exercise of the right of access to information before PAIA was passed and after PAIA was passed to highlight the anomaly of the application of Section 7. This paper argues that Section 7 unconstitutionally limits the ambit of the right of access to information and a direct constitutional challenge on this provision is necessary.